The oxidative reforming of methane to synthesis gas on a commercial steam reforming catalyst - Theron, Johannes Nicolaas (Department of Chemical Engineering, 2023)
The oxidative reforming of methane to predominantly carbon monoxide and hydrogen was studied over a commercial steam reforming catalyst. The said reaction was performed in an integral fixed-bed reactor at temperatures between 575°C and 650°C at a total pressure of 200 kPa(a). The primary objective of the study was the design and construction of equipment to facilitate firstly, the measurement of axial bed temperature profiles, and secondly, the investigation of transport effects during the oxidative reforming of methane. The absence of internal or external temperature- and concentration gradients were tested by subjecting the experimental results to theoretical criteria that had previously been derived to check for transport limitations. In all cases the correlations confirmed that the experimental system was free of transport resistances. Having obtained differential reaction rates from the integral data, two LangmuirHinshelwood models were developed and fitted to the data. The model which was derived from the assumption that methane adsorption on a single active site was the rate-determining step, gave the best fit to the experimental data. Adsorption constants correlated in broad terms with the reaction orders of the species which were previously determined by the method of initial rates. The differential kinetic data that were obtained from the fitting of exponential curves to the integral data gave the best correlation between predicted and measured reaction rates. Subsequent to the differential treatment of the data, an attempt was made to correlate the integral data by means of an integral reaction model. A combination of the total oxidation-, oxidative reforming- and steam reforming of methane, as well as the water-gas shift reaction, resulted in the best fit between measured- and predicted data. The predicted methane, carbon monoxide- and hydrogen partial pressures correlated well with experimental data, but that of oxygen, carbon dioxide and water were less accurately predicted by the model. The lack of any comparable study in the literature made it impossible to compare adsorption- and rate constants to other work. X-ray diffraction results showed that the active catalyst bed consisted of a top layer of nickel oxide on alumina and zero-valent nickel on alumina deeper into the bed. Evidence from thermogravimetric experiments revealed that carbon formation was inhibited by H2 cofeeding and high 0 2 inlet partial pressures, but that it was enhanced by CO co-feeding.